SIMULASI PENGARUH KECEPATAN UDARA FLUIDISASI TERHADAP VOLUME FRACTION PADA GASIFIKASI DUAL REAKTOR FLUIDIZED BED MENGGUNAKAN SOFTWARE CPFD BARRACUDA VIRTUAL REAKTOR - Wibisono, Muhammad Yusuf; Winaya, I Nyoman Suprapta; Suryawan, I Gede Putu Agus (Teknik Desain Mekanika; Vol 13 No 4 (2024): Oktober 202 :4 Teknik Desain Mekanik, 2024)
Abstract Gasification issthe process offconverting soliddor liquid feedstockkinto useful gaseoussfuel orrchemical feedstock thattcan easily beeburned toorelease energyyor used forrthe production of value-addeddchemicals. Gasificationnrequires a gasificationnagent, such as air, oxygen, orrsteam, toorestructure theemolecular structure of the feedstock and convert it intoouseful gaseous fuellwith a higherr(H/C) ratio. The development of gasification technology has been extensive, one of which is the dual reactor fluidized bed (DRFB) technology. This technology utilizes two reactors: the combustion reactor and the gasification reactor. This study aims to analyze the influence of various air fluidization velocities on the volume fraction in a Dual Reactor Fluidized Bed (DRFB). The research method employed simulation using CPFD Barracuda Virtual Reactor software. The design used in this simulation is a dual reactor fluidized bed, with RDF fuel ranging in size from 0.2-0.4 mm. The material bed used is silica sand with a size range of 0.1-0.2 mm. This study utilized three air velocity variations: 12 m/s, 13 m/s, and 14 m/s. The research results indicate that as the air velocity increases, the resulting volume fraction decreases. The 12 m/s velocity variation yields a higher volume fraction value compared to the 14 m/s velocity. Keyword: Gasification, Dual Reactor Fluidized Bed, RDF, Simulation, Volume Fraction